The Influence of Quantum Teaching and Interaction Models Social To Performance Study Students in Social Sciences Lessons in class VA SDN 08 Bungku - Hennimawati; Iskandar; Herlina (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Continuous developments in the world of education changed in a way significant , so Lots change pattern think educator from the common and rigid to more modern ones , p it is very influential to progress of education in Indonesia. Problem Formulation How the influence of the Quantum Teaching model on performance Study student in social studies lessons in the VA SDN 08 Bungku class , how influence interaction social to performance Study student in social studies lessons in the VA class of SDN 08 Bungku . is results Study students who have interaction social tall more Good than students who have interaction social low If using the Quantum Teaching model. Purpose For analyze exists the influence of the Quantum Teaching model on performance Study students in social studies learning in class VA SDN 08 Bungku . For analyze exists influence interaction social to performance Study students in social studies learning in class VA SDN 08 Bungku . For identify and analyze difference results Study students who have interaction social high and interaction social low If using the Quantum Teaching model. Types of research This that is study quantitative with use method experiment . On research experiment This writer use One class experiment . Research results Tools used For collect data on research must suitable and capable measure with appropriate what do you want measured , so that the data obtained can trusted or valid.